Homocysteine Metabolism in Children with Idiopathic Nephrotic Syndrome. Issue 2 (23rd January 2014) - Kundal, Mohan; Saha, Abhijeet; Dubey, N.K.; Kapoor, Kanika; Basak, Trayambak; Bhardwaj, Gaurav; Tanwar, Vinay Singh; Sengupta, Shantanu; Batra, Vinita; Upadhayay, Ashish Dutt; Bhatt, Ajay
Abstract Background Homocysteine metabolism is altered in children with idiopathic nephrotic syndrome. Hyperhomocysteinemia is a risk factor of early atherosclerosis and glomerulosclerosis and may occur at time of first occurrence of idiopathic nephrotic syndrome. Methods Thirty children with first episode of idiopathic nephrotic syndrome (FENS) aged 1–16 years along with 30 age‐ and sex‐matched healthy controls were enrolled in this study. Homocysteine and cysteine were measured with HPLC; vitamin B12 and folic acid were measured with electro‐chemilumiscence immunoassay. Primary outcome measure was plasma homocysteine level in children with FENS and in controls. Secondary outcome measures were (1) plasma and urine homocysteine and cysteine levels in children with FENS at 12 weeks and 1 year (remission) and (2) plasma and urine levels of vitamin B12 and folic acid in children with FENS, at 12 weeks and 1 year (remission). Results Plasma homocysteine and cysteine levels were comparable to controls in children with FENS, at 12 weeks and 1‐year remission. Plasma levels of vitamin B12 and folic acid were significantly decreased compared to controls in FENS due to increased urinary excretion, which normalize during remission at 12 weeks and 1 year. Urinary homocysteine and cysteine levels were significantly raised in FENS compared to controls and continued to be raised even at 12‐week and 1‐year remission. Conclusion Homocysteine metabolism is deranged in children with FENS. Renal effects of long‐term raised urinary homocysteine levels need to be studied.